Macroeconomic Developments and Prospects in Low-Income Developing Countries-2019. (Policy Papers; Policy Paper ;, 2019)
This paper is the fifth in a series that examines macroeconomic developments and prospects in low-income developing countries (LIDCs). LIDCs are a group of 59 IMF member countries primarily defined by income per capita below a threshold level. LIDCs contain one fifth of the world's population-1.5 billion people-but account for only 4 percent of global output. The first chapter of the paper discusses recent macroeconomic developments and trends across LIDCs and, using growth decompositions, explores the key drivers of growth performance in LIDCs. A second chapter examines the challenges faced by LIDCs in implementing a value-added tax system, generally seen as a key component of a strong national tax system. The third chapter discusses how financial safety nets can be appropriately tailored to the specific needs of LIDCs, recognizing that an effective safety net is important for ensuring financial stability and underpinning public confidence in the financial system, thereby promoting financial intermediation.